Relações de gênero no trabalho docente : um estudo de caso no Colégio Estadual Atheneu Sergipense - Dias, Alfrancio Ferreira (2013)
This research aimed to understand the changes experienced in recent years of teaching work in high school of Atheneu Sergipense State College in the city of Aracaju/SE, in order to assess changes in social relations of gender, in the expansion of citizenship and rights of the teachers. It was intended also to analyze the relations of gender in teaching work as a space designed as a social relation that incorporates the issue of the meanings and senses attributed to work by the teachers from social practices. The methodological choice fell on a qualitative approach, because it helps to express the sense of social phenomena and the understanding of the meanings of human actions and relations. The case study proved relevant to the knowledge of concrete situations of work of the teachers, what for, through the social relationships observed, can be singled out elements able to inform analyzes that would contribute to a better understanding of the changes in social relations of gender. The approach of the type case study was considered relevant to seek, in representational relation, cognitive and affective mechanisms of the elaboration of social representations of women and men teachers. Different sources of information were consulted in order to produce knowledge about the object, from data collection, such as official documents and statistics. Questionnaires were administered to 38 teachers (22 women and 16 men); semi-structured interviews conducted with 16 teachers (eight women and eight men), to analyze the dialectic of the work process, taking gender as a category of analysis. The results report that women and men teachers of the high school of Atheneu Sergipense State College attribute different senses and meanings to work and qualification. This happens according to the definition of the seats allocated to men and women, the trajectory of work and family, and the aspects that influence in the construction of projects and personal and professional expectations, which become experienced differently by men and women.